What is Next in Anion‐Exchange Membrane Water Electrolyzers? Bottlenecks, Benefits, and Future - Santoro, Carlo; Lavacchi, Alessandro; Mustarelli, Piercarlo; Di Noto, Vito; Elbaz, Lior; Dekel, Dario R.; Jaouen, Frédéric (ChemSusChem, 2022)
As highlighted by the recent roadmaps from the European Union and the United States, water electrolysis is the most valuable high‐intensity technology for producing green hydrogen. Currently, two commercial low‐temperature water electrolyzer technologies exist: alkaline water electrolyzer (A‐WE) and proton‐exchange membrane water electrolyzer (PEM‐WE). However, both have major drawbacks. A‐WE shows low productivity and efficiency, while PEM‐WE uses a significant amount of critical raw materials. Lately, the use of anion‐exchange membrane water electrolyzers (AEM‐WE) has been proposed to overcome the limitations of the current commercial systems. AEM‐WE could become the cornerstone to achieve an intense, safe, and resilient green hydrogen production to fulfill the hydrogen targets to achieve the 2050 decarbonization goals. Here, the status of AEM‐WE development is discussed, with a focus on the most critical aspects for research and highlighting the potential routes for overcoming the remaining issues. The Review closes with the future perspective on the AEM‐WE research indicating the targets to be achieved. Water electrolysis: In this Review, the advantages and challenges of anion‐exchange membrane water electrolyzers are discussed. The status of their development with a focus on the most critical aspects for research is presented, highlighting the potential routes for overcoming the remaining issues, and future targets to be achieved are also presented.